Type theft especially bold in the code criminal from 1969 and current – evaluation comparative - Wilk, Leszek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
In the code criminal case of 1969 appeared for the first time first new type theft specified statutory as theft " especially audacious." The concept is not left By at that time legislator defined, which meant that trouble interpretation he rested on doctrine and case law. Despite their efforts , this concept remained blurry, as a result what this guy theft NO appeared myself already in the code Criminal Code of 1997. Legislature he reminded about it in 2019 and again introduced it into the code , providing at the same time in a spacious way definition statutory. It could myself therefore seem that this Together type theft especially audacious as statutory defined fulfilled will be requirements warranty sufficient specificity recipe criminal. Answer on question - is it so ? it really is a task this studies.